2012
DOI: 10.1007/s12098-012-0851-4
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in Children and Adolescents: Epidemiology and Pathogenesis

Abstract: High blood pressure is one among the leading contributors to burden of disease globally. Approximately 54 % of stroke and 47 % of ischemic heart disease events worldwide were attributable to high blood pressure in the year 2001. There is deficiency of data on the long-term outcome of hypertension in children. In spite of this, there is sufficient evidence to suspect that the health risks of hypertension in pediatric patients are substantial. Hypertension in childhood is known to result in hypertension in young… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 41 publications
1
14
0
Order By: Relevance
“…1 Almost 80 million U.S adults are suffering with High blood pressure currently. With less than half of those are having controlled Hypertension, 62% of Cardio vascular diseases and 49% of Ischemic heart disease are caused due to uncontrolled Hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…1 Almost 80 million U.S adults are suffering with High blood pressure currently. With less than half of those are having controlled Hypertension, 62% of Cardio vascular diseases and 49% of Ischemic heart disease are caused due to uncontrolled Hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…In India a survey of 24,842 school children in the age group 5 to 16 years where blood pressure data was available for 20,263 students. Hypertension by single measurement was diagnosed in 10.10 % of those with normal weight, 17.34 % in the overweight and 18.32 % in the obese (4). A study from Iran on 21,111 children in the age group of 6 to 18 years showed overall 7.7 % prevalence of systolic and diastolic hypertension (7).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is evidence that children with mildly elevated blood pressure (BP) are at increased risk for developing adult hypertension (3). Evidence of target organ damage, such as left ventricular hypertrophy (LVH) and pathological vascular changes have been found even in children with a recent diagnosis of high BP (4). Therefore, study on prevalence and early diagnosis of hypertension in childhood is an important strategy for promoting public health and prevention of cardiovascular diseases.…”
Section: Introductionmentioning
confidence: 99%
“…It is described as HT, in which there are no secondary causes of increased BP [4]. The essential hypertension is a highly heterogeneous disease and does not have one assigned pathomechanism, however it is considered a result of coexistence of many pathologic factors [5,6].…”
Section: Introductionmentioning
confidence: 99%